2020
DOI: 10.1177/0022034520943574
|View full text |Cite
|
Sign up to set email alerts
|

Interventions to Reduce Aerosolized Microbes in Dental Practice: A Systematic Review with Network Meta-analysis of Randomized Controlled Trials

Abstract: The aim of this systematic review and network meta-analysis was to identify and rank the effectiveness of different interventions used in dental practice to reduce microbial load in aerosolized compounds. Seven electronic databases were searched to April 6, 2020, for randomized controlled trials (RCTs) or nonrandomized prospective studies in the field. Study selection, data extraction, and risk-of-bias assessment were performed for all included studies, while the outcome of interest pertained to differences in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
62
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(67 citation statements)
references
References 49 publications
0
62
0
5
Order By: Relevance
“…Particulate generation during routine procedures in dental practice is one of the major concerns for clinical dentistry and one that contributes knowledge to the general notion regarding potentially hazardous aerosolized material after application of certain procedures in everyday clinical practice. Prior investigations have highlighted the pathogenic load of bio-aerosols in dentistry [33], or undertaken endorsements to identify potentially effective measures against bio-aerosol content from a microbiologic perspective [34]. This becomes especially alarming under the light of the severe acute respiratory syndrome-coronavirus-2 (SARS-CoV-2) pandemic [35], where healthcare workers are in the frontline of suspended droplet or aerosol-related contamination and inhalation/respiration protection measures are crucial [36].…”
Section: Findings In Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…Particulate generation during routine procedures in dental practice is one of the major concerns for clinical dentistry and one that contributes knowledge to the general notion regarding potentially hazardous aerosolized material after application of certain procedures in everyday clinical practice. Prior investigations have highlighted the pathogenic load of bio-aerosols in dentistry [33], or undertaken endorsements to identify potentially effective measures against bio-aerosol content from a microbiologic perspective [34]. This becomes especially alarming under the light of the severe acute respiratory syndrome-coronavirus-2 (SARS-CoV-2) pandemic [35], where healthcare workers are in the frontline of suspended droplet or aerosol-related contamination and inhalation/respiration protection measures are crucial [36].…”
Section: Findings In Contextmentioning
confidence: 99%
“…Based on theoretical grounds and some perspectives, water cooling during composite grinding has been proposed, as a measure that could potentially contribute to the formulation of increased particle size, with nano-sized dust particulates being trapped to larger water droplets, thus offering enhanced protection against nano-particle respiration and penetration of sensitive human organs [1,31]. However, one should effectively consider the potential for generation of pronounced aerosol in dental settings, when water cooling practices are followed, as well as the possibility of increased pathogen diffusion via this route [34]. Additionally, research in the field of orthodontics revealed an increased amount of particulate production after high-speed, water supplemented adhesive grinding following fixed appliance therapy [29].…”
Section: Findings In Contextmentioning
confidence: 99%
“…17,[24][25][26][27][28][29][30][31][32][33][34] Largescale efforts have been lately endorsed to collectively appraise all available evidence and provide justifiable ranking of the efficiency of these methods. 35,36 The most prevalent recorded approaches were preprocedural mouth rinse using a wide variety of potentially antimicrobial agents, such as, chlorhexidine (CHX) 0.12%, CHX 0.2% or tempered CHX 0.2%, cetylpiridinium chloride 0.05%, povidone iodine (PI) 1%, chlorine dioxide, herbal-based agents, or others pertaining to ozone irrigation, use of high volume evacuators and/or dental isolation systems, or agents added to DUWLs to reduce the load. 27,28,37,38 Evidence from a study on bacterial load during orthodontic procedures comparing bracket debonding followed by enamel clean-up with high-speed handpiece and water cooling versus standard orthodontic care involving archwire and/or ligature change, and replacing procedures, highlighted the increased pathogenic state of aerosols produced by the former, with a mean difference of 49.2 (95% CI, 19.4-79.0) in total CFUs.…”
Section: Microbiologic Considerations and Bio-aerosolsmentioning
confidence: 99%
“…Among the priority treatments of choice and apart from CHX solutions (either tempered or nontempered), PI 1% has also been considered a viable alternative. 35,36 Aforementioned documented evidence originates, as discussed, primarily from ultrasonic scaling clinical studies, randomized in most cases, while total bacterial count in generated aerosol has been the outcome of interest, leaving virus load aside. Extrapolation to other potentially producing aerosolized compounds procedures, however, seems reasonable within a dental cabinet setting and certain orthodontic procedures, such as fixed appliance debonding, may benefit from such measures.…”
Section: Microbiologic Considerations and Bio-aerosolsmentioning
confidence: 99%
See 1 more Smart Citation